LITERACY AND NUMERACY THROUGH KAMPUS MENGAJAR IN ELEMENTARY SCHOOLS TO SUPPORT THE MERDEKA BELAJAR CURRICULUM - Hakim, Nurul Fahmi Arief; Nur A, Citra; Kurniasih, Nia; Syifani Nur’aini, Tiara (LPPM Univ. Ibn Khaldun Bogor, 2023)
Merdeka Belajar program was launched as a government effort to improve the quality of education in Indonesia and face increasingly complex and dynamic global challenges. The educational problems at SDN 143 Kopo are the lack of optimal literacy and numeracy activities for students and the limited human resources to deal with a large number of students. The method used in this activity is the direct learning assistance method, where Kampus Mengajar (KM) students act as facilitators in helping students deal with difficulties encountered in learning. Each step taken will be explained descriptively. The flow of an implementation of activities made using 4 stages, namely observation, preparation, implementation, and evaluation has been going well. In practice, the planned work program for elementary school students includes the “Gerakan Literasi dan Numerasi” (GLS), creating reading corners, reciting activities, and teaching English. The result obtained is an increase in students' enthusiasm for learning, especially in literacy and numeracy skills. Students begin to be able to recognize letters, read and count with the help KM5 students. The planned work program can run with the help of KM5 students. The existence of KM5 students makes students more enthusiastic and enthusiastic in teaching and learning activities.